Regional specificity in small business in Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
The current state of business is characterized by regional differences. Each region has a corresponding potential (industrial, financial, resource, labor, etc.) that causes the vast development of certain sectors of the small business. If you look by region, it is possible to say about the rather uniform development of small businesses. As expected, far from Almaty and Astana took the lead in the number of registered entrepreneurs. Good results show East Kazakhstan, Karaganda and South Kazakhstan region, while in the rest of the level of development of small enterprises is low. Conducted an analytical review emphasizes the need for further study of regional peculiarities of small business in Kazakhstan in order to adjust and improve the environment for small businesses how to use financial and non-financial instruments.
Keywords: business; entrepreneurship; region; capital; plant and equipment; analysis; finance; enterprise; company; money; income; expenses; losses; financing strategy.